Analisis Sumber Daya Pembelajaran Bilingual dalam Meningkatkan Kualitas Pendidikan Sekolah Dasar - Aurora, Ainnur Ratri; Nuraini, Widya; Nuha, Khana Ulin; Afifah, Naura Nisrina; Dewi, Avianita; Widagdo, Arif (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the management of bilingual learning resources in improving the quality of primary education. Using a literature review method, this article examines previous research related to the implementation of bilingual education, particularly focusing on teacher readiness, student engagement, and supporting facilities and infrastructure. The findings indicate that the success of bilingual learning heavily relies on teachers' competence in delivering instruction in two languages, the use of contextual and enjoyable learning approaches for students, and the availability of adaptive media and curriculum. This article recommends strengthening teacher training, encouraging active student participation, and optimizing the use of local resources and technology as solutions to the challenges faced in implementing bilingual education in Indonesia.